Relational State Capacity: Conceiving of Relationships as a Core Component of Society’s Ability to Achieve Collective Ends - and Honig, Dan; Krishnamurthy, Mekhala; Sharma, Rahul Karnamadakala (Johns Hopkins University, 2025)
Relational state capacity (RSC) integrates the quality of citizen-state relationships into the concept of state capacity, emphasizing mutual recognition between citizens and state agents as foundational for societal problem-solving. Traditional state capacity definitions overemphasize technical and institutional elements, overlooking relational dynamics. RSC is a latent societal resource activated through mutual recognition in citizen-state exchanges with potential to improve outcomes across diverse domains, from public health to social cohesion. We have for too long transactionalized governance; we need instead to collectively invest in intentional structures and practices that foster relationality. Drawing on insights from existing literature, the paper explores how RSC is built, intermediated, and shaped by broader societal norms and organizational dynamics. By making RSC legible as an object of inquiry, the paper lays the groundwork for empirical investigation into RSC’s causal pathways, spillover effects, and resilience to disruption. There are many pathways for theoretical and empirical development in this emergent field; focusing on the relational in understanding state performance has the potential to enhance citizens’ welfare, strengthen democratic resilience, and improve public sector performance.